Pembelajaran Pementasan Teater dengan Metode Role Playing Berbasis Project Learning Bagi Mahasiswa Tbi IAI Al-Qolam - Zuhri, Syaifudin; Kholik, Kholik (Jurnal Pembelajaran Sastra, 2021)
One of the competencies that must be possessed by students of the Indonesian Language Education Study Program, especially at IAI Al-Qolam, is that students are able to perform theater performances. The curriculum of the Indonesian Language and Literature Education study program also requires students to take Theater Performance courses in the fifth semester. The competency will be mastered by students if they are able to performe based on project learning using the role playing method. Project learning will provide a real stage experience, they will be able to apply various theories related to theater that were previously taken in the Literary Studies course. The role playing method helps students become skillful in a theater performance. The capability of acting is a very important factor, because a character in a theater will have a better performance if the character is able to live up to every role he gets after casting. The role playing method is an effort to improve theater playing skills for students of the Indonesian Language Education Study Program at IAI Al-Qolam, which is expected to be an effective and fun learning method, so that students are motivated to play theater well.